Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Eastern Pearl Flour Mills Makassar - Azhary Ismail; Andi Nuryadin; Rina; Ansar Mulkin Bas; Nurmega; Andi Hendra Syam (Jurnal Online Manajemen ELPEI, 2023)
Competition between companies in the current era is getting higher both in the trade and service industries, so companies need to improve their performance in all fields, both in terms of increasing finance, technology and human resources. To prove the hypothesis that has been put forward, this study used: a. Simple Linear Regression Analysis To determine the magnitude of the influence of the work environment on the productivity of production employees at PT. Eastern Pearl Flour Mills Makassar with the formula: Y a + bx + e Description: X Organizational Culture Y Employee Performance a Constant number e Error standard results from research that has been conducted and processed to determine the effect of Organizational Culture on employee performance at PT Eastern Pearl Flour Mills Macassar. research results that have been described in the previous chapter. there is a significant influence of organizational culture on employee performance at PT Eastern Pearl Flour Mills Makassar with a significance level of (0.000 0.1) so that Ha is accepted and Ho is rejected.